Daily patterns in parasite processes: diel variation in fish louse transcriptomes. Issue 8 (July 2022) - Hunt, R.; Cable, J.; Ellison, A.
Graphical abstract: Highlights: Parasites likely time themselves to daily host or environmental rhythms. We studied the fish louse Argulus foliaceus transcriptome over day-night cycles. Approximately 50% of annotated lice genes showed significant daily rhythms. Rhythmic gene functions included feeding, development, and potential drug targets. This provides important resources for application of chronotherapy in fish lice. Abstract: Parasites, similar to all other organisms, time themselves to environmental cues using a molecular clock to generate and maintain rhythms. Chronotherapeutic (timed treatment) techniques based on such rhythms offer great potential for improving control of chronic, problematic parasites. Fish lice are a key disease threat in aquaculture, with current control insufficient. Assessing the rhythmicity of fish lice transcriptomes offers not only insight into the viability of chronotherapy, but the opportunity to identify new drug targets. Here, for the first known time in any crustacean parasite, diel changes in gene transcription are examined, revealing that approximately half of the Argulus foliaceus annotated transcriptome displays significant daily rhythmicity. We identified rhythmically transcribed putative clock genes including core clock/cycle and period/timeless pairs, alongside rhythms in feeding-associated genes and processes involving immune response, as well as fish louse drug targets. A substantial number of gene pathways showed peak transcription in hours immediately preceding onset of light, potentially in anticipation of peak host anti-parasite responses or in preparation for increased feeding activity. Genes related to immune haemocyte activity and chitin development were more highly transcribed 4 h post light onset, although inflammatory gene transcription was highest during dark periods. Our study provides an important resource for application of chronotherapy in fish lice; timed application could increase efficacy and/or reduce dose requirement, improving the current landscape of drug resistance and fish health while reducing the economic cost of infection.